Building a phenomenological chain-level understanding of mechanics of semicrystalline polymers: 1. Experimental - Smith, Travis; Gupta, Chaitanya; Siavoshani, Asal Y.; Wang, Shi-Qing (Polymer (Guilford), 2023)
The current understanding of mechanical behavior of semicrystalline polymers (SCPs) is insufficient even at a qualitative level. Since a disproportional extent of efforts have been made to describe yielding rather than brittle fracture or lack of drawability in SCPs, we have avoided basic questions such as when and why tensile extension of SCPs result in brittle failure. Consequently, it has remained ambiguous just exactly what crystallization does, e.g., whether crystallization favors ductile or brittle mechanical response, what polymer entanglement does in the crystalline state, and exactly how and why tie-strands play an essential role to bring about yielding and ductility in SCPs. The present work (in a sequence of two papers) builds a coherent phenomenological basis to propose a chain-level qualitative framework where answers to these questions start to emerge. We first present extensive data in Paper 1 to (a) show how ductility depends on the state of crystallization, (b) describe a ductile-to-brittle (non-drawable) transition as a function of temperature and drawing rate, including the anomalous temperature and rate dependences, and (c) demonstrate how the structures of SCPs may be affected by pre-deformation to improve ductility and increase tensile strength. While some observations appear familiar, the total phenomenology has never been holistically compiled to depict a comprehensive (qualitative) molecular picture in Paper 2 that elucidates the effect of crystallization and the roles of chain entanglement and tie-strands regarding drawability. As example of complication of mechanical behavior of semicrystalline polymers, a polypropylene (random copolymer of PP) and a polyhydroxyalkanoates show opposite temperature dependence of their ductility. [Display omitted] •Mechanical behavior of semicrystalline polymers (SCPs) is studied to gather comprehensive phenomenology. The study shows not only when drawability is lost, but also how pre-deformation can bring back ductility.•Most phenomena have been known for decades, but some anomalous features illustrate that the subject under study is complicated.•major theme of this paper (Paper 1) is to illustrate when and how SCPs become brittle. Subsequent Paper 2 provides a qualitative account of SCP ductility vs. loss of drawability.